2005
DOI: 10.1159/000084631
|View full text |Cite
|
Sign up to set email alerts
|

Thwaites’ Diagnostic Scoring and the Prediction of Tuberculous Meningitis

Abstract: Objective: This study was conducted to investigate the applicability of Thwaites’ diagnostic criteria in order to differentiate tuberculous from bacterial meningitis. Material and Methods: The study was done retrospectively in HIV-negative patients (n = 126) with meningitis. Of the 126 patients, 103 had bacterial meningitis and 23 patients had tuberculous meningitis. The diagnosis was confirmed microbiologically in 59 and 12 patients with bacterial and tuberculous meningitis, respectively. The prediction of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 11 publications
1
30
0
5
Order By: Relevance
“…TDI allowed differentiating bacterial meningitis from TBM based on 5 criteria weighted by a score including age, duration of symptoms, peripheral blood WCC, CSF WCC, and CSF percentage of neutrophils [9]. Assessment of TDI in different studies including non-HIV adults patients showed sensitivity from 95.6% to 99% and a specificity from 70.8% to 80% [26, 27]. However, specificity is too low when test was applied in high HIV prevalence setting [28].…”
Section: Discussionmentioning
confidence: 99%
“…TDI allowed differentiating bacterial meningitis from TBM based on 5 criteria weighted by a score including age, duration of symptoms, peripheral blood WCC, CSF WCC, and CSF percentage of neutrophils [9]. Assessment of TDI in different studies including non-HIV adults patients showed sensitivity from 95.6% to 99% and a specificity from 70.8% to 80% [26, 27]. However, specificity is too low when test was applied in high HIV prevalence setting [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thwaites established a scoring system employing 143 cases of TBM and 108 cases of BM by regression analysis; this scoring system was evaluated by Sunbul et al (9) using 23 cases of TBM and 103 cases of BM; their evaluation revealed the sensitivity and specificity of the system to be 95.6z and 70.8z, respectively. The current study showed that the sensitivity of Thwaites' diagnostic scoring system for the differential diagnosis of TBM and BM was 98.2z, but its specificity was only 43.6z, which is much lower compared with previous studies (5,9). Hence, BM patients were divided into initially treated (BM2) and partially treated (BM1) groups according to their intake of antibiotics before admission.…”
Section: Discussionmentioning
confidence: 99%
“…Thwaites’ diagnostic scoring was evaluated in a retrospective study by Sunbul et al [12] who reported sensitivity and specificity rates of 95.8 and 71.6%, respectively. However, in microbiologically proven patients, the sensitivity decreased to 91.7% and the specificity increased to 79.7%.…”
Section: Discussionmentioning
confidence: 99%